Open source software governance: Distilling and applying industry best practices - Harutyunyan, Nikolay (Ernst Denert Award for Software Engineering 2020, 2022)
Modern software architectures are becoming increasingly complex and interdependent. The days of exclusive in-house software development by companies are over. A key force contributing to this shift is the abundant use of open source frameworks, components, and libraries in software development. Over 90% of all software products include open source components. Being efficient, robust, and affordable, they often cover the non-differentiating product requirements companies have. However, the uncontrolled use of open source software in products comes with legal, engineering, and business risks stemming from incorrect software licensing, copyright issues, and supply chain vulnerabilities. While recognized by a handful of companies, this topic remains largely ignored by the industry and little studied by the academia. To address this relevant and novel topic, we undertook a 3-year research project into open source governance in companies, which resulted in a doctoral dissertation. The key results of our work include a theory of industry best practices, where we captured how more than 20 experts from 15 companies worldwide govern their corporate use of open source software. Acknowledging the broad industry relevance of our topic, we developed a handbook for open source governance that enabled practitioners from various domains to apply our findings in their companies. We conducted three evaluation case studies, where more than 40 employees at three Germany-based multinational companies applied our proposed best practices. This chapter presents the highlights of building and implementing the open source governance handbook.
CRIS-Team Scopus Importer:2024-12-16